PENGARUH PROMOSI, TERHADAP KEPUTUSAN PENGGUNAAN ELECTRONIC DATA CAPTURE (EDC) DIMEDIASI OLEH PENGETAHUAN DAN KEPERCAYAAN MERCHANT DI PT BANK NEGARA INDONESIA KANTOR CABANG MUSI PALEMBANG - M. Erkan Fadjruddinsya; Sri Rahayu; Dia Isnaini Asiati (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
This research has research objectives based on the formulation of the problem. First to find out and analyze the effect of promotion, knowledge and trust of merchants on the decision to use EDC services at PT Bank Negara Indonesia Musi Palembang Branch Office. Second, to find out and analyze the effect of promotion on decision making on the use of EDC services with merchant knowledge as an intervening variable at PT Bank Negara Indonesia Musi Palembang Branch Office. The design used in this research is descriptive-analysis research design. Path analysis technique is carried out to see the effect of Promotion (X1), Merchant Knowledge (Y1), Merchant Trust (Y2) on the Decision to Use EDC (Z). The results of the study above indicate that the promotion variable influences the EDC decision variable of 0.257. Merchant Knowledge Variable influences the EDC Decision variable of 0.208. The Merchant Trust Variable influences the EDC Decision variable of 0.461. Estimation results obtained that the value of the Promotion variable of 0.616 and the value of the intermediary variable Merchant Knowledge of 0.312 produces the value of the EDC Usage Decision variable of 0.192192. The promotion variable value is 0,670 with the coefficient value on the intermediary variable Merchant Trust is 0,256 so it produces the EDC Usage Decision variable value of 0,17152